The discovery of Brazil seen by Brazilian newspapers: The gradual actualisation of social memory - Naiff, Denis Giovani Monteiro (2004)
The present paper looks for the description of the gradual participation of part of the Brazilian media in the process of update of social memory of the discovery of Brazil, through the analysis of the matters transmitted by the daily written press regarding the discovery, concerning the beginning of the colonization process and the commemoration of the fifth centennial. Data collection of matters, run during three consecutive years January 1, 1998, until December 31, 2000), was undertaken in four newspapers of great circulation in the city of Rio de Janeiro: Jornal do Brasil, O Globo (representative newspapers of Rio de Janeiro), Folha de São Paulo (representative of the middle classes and average-high class of Rio de Janeiro readers) and O Dia (a popular newspaper). The coding instruments of the matters included the following items: (1) formal aspects, discursive form, authorship and their sources of information, origin of the information (national, Portuguese or other country) and mentioned institutions; (2) substantive content, focusing the privileged spheres (political / economical, religious, cultural / artistic, historical, educational / scientific), the categories of involved historical subjects, the descriptive or analytical treatment; (3) pertinence of the matter, i. e., if it possesses direct or allusive reference to the theme; (4) underlying communicative orientation, in terms of valorization or opinion relatively to the discovery of Brazil, with the use of the distinction done by S. Moscovici among diffusion, propagation and propaganda. The global analysis shows that, during the whole analyzed period, the transformations are slow, happening mainly on formal aspects, as the gradual increase of the number of articles and reports, and as for the pertinence of the matters with the decrease of those just allusive. Only in the first semester of the 2000, with the approach of the date of the fifth centennial (April 22), significant inflections are observed in the development curves, that indicate the introduction of new knowledge and polemical judgements in the process of updating of the social memory of the discovery. The main results show that: (1) the predominant substantive contents stop being the commemoration of the facts and of the historical facts in itself, while the related contemporary themes start to acquired larger importance in average; (2) the Portuguese navigators give up the place of main historical subjects focused by the media and are substituted by the Indians, in function of the repercussion of the popular manifestations against the official commemorations; (3) there is an increase in the amount of analyses and critical judgements regarding the discovery of Brazil, that characterize an underlying orientation of propaganda, associated to a decrease of the diffusion matters, i. e., don't possess explicit position standings. The updated social memory of the discovery becomes, at the end of the period, more complex and politically polarized.  DOI: http://dx.doi.org/10.17575/rpsicol.v17i2.453